Floristic composition and diversity of plants across three vegetation zones of Gashaka Gumti National Park, northeastern Nigeria - Hammanjoda, Salihu Abba; Nulit, Rosimah; Chee, Kong Yap; Nformi, Umaru Buba; Nodza, George; Saba, Abdulwakil Olawale; Besi, Edward Entalai; Go, .Rusea (Universiti Putra Malaysia, 2025)
Gashaka Gumti National Park (GGNP) is Nigeria’s biggest national park, with an elevation range of 300 m to its highest peak at 2400 m. Although GGNP has a wide range of plant species, particularly woody ones, there is limited information regarding its floristic composition along the vegetation zones. This study examined the floristic composition and species diversity of GGNP by systematically sampling plant species using quadrats of 25 m × 25 m and a point-centered quadrat (PCQ). A total of 228 plant species belonging to 114 genera and 49 families were recorded across the three major vegetation zones. Fabaceae was the most species-rich family (34 species), representing 14.9% of the species, followed by Malvaceae (18 species), representing 7.9%. Other important species include Moraceae and Rubiaceae, 15 species each, representing 6.6% of the species, respectively, while Combretaceae (10 species) represents 4.4% of the species recorded. The Lowland Tropical Rain Forest (LTRF) recorded 137 species in 42 families, and Montane Highland (MH) recorded 146 species in 43 families. In comparison, the Savannah Woodland (SW) recorded 68 species in 28 families. Twenty-five species, which account for 11% of the total, are threatened. Among them, 10 species are Vulnerable, six are Endangered, five are Critically Endangered, and four are Near Threatened, according to the International Union for Conservation of Nature (IUCN) Red List status. Across all plots, average Shannon-Weiner’s species diversity indices of 2.40, 2.40, and 2.25 were recorded for MH, LTRF, and SW, respectively. According to Sorensen’s similarity coefficient, LTRF and SW (33.42%) habitats recorded the highest species similarity, while MH, as against SW habitats, recorded the lowest (18.92%). The importance value indicated that the SW had the most important species based on the importance value (0.581) compared to other vegetation zones. The overall evenness values for LTRF, SW, and MH are 0.77, 0.78, and 0.77, respectively. This study offers significant insights into the flora variety and conservation situation of Gashaka Gumti National Park. It emphasizes the need for more research and conservation initiatives to save its distinct habitats and endangered species.